Teknik Komunikasi Persuasif Ahmad Rifa’i Rif’an Dalam Dakwah Kepada Kalangan Milenial - Azlika Purnama Sari, Nur Aida (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The millennial generation is one of the priority mad'u groups to be preached. Through proper preaching, a generation that upholds religious values ​​and morality will be formed so that they are ready to work on the rare momentum of the demographic bonus. Ahmad Rifa'I Rif'an is one of the Da'Is who have successfully preached among Millennials. Through a book entitled